PERANCANGAN WEBSITE OBJEK WISATA PEMANDIAN UMBUL MABAR KABUPATEN SIMALUNGUN UNTUK MENINGKATKAN JUMLAH PENGUNJUNG - Juliani, Fitri; Oktopanda; Merry (Akademi Manajemen Informatika dan Komputer PARBINA NUSANTARA Pematangsiantar, 2025)
The Umbul Mabar Baths in Marihat Bandar Village, Simalungun Regency, is one of the tourist attractions that has great potential to attract tourists, both local and foreign. However, limited access to information about this tourist attraction means that the number of visitors is not optimal. Therefore, designing a website as a digital promotional media is expected to be an effective solution to increase the number of visitors to the Umbul Mabar Baths. This study aims to design and develop an informative and user-friendly website, in order to facilitate access to information for potential visitors. The design process includes user needs analysis, interface design, content development, and implementation of interactive features. This website will provide complete information about the Umbul Mabar Baths, including history, natural beauty, facilities, entrance fees, and routes to the location. The interactive features embedded in the website include a location map integrated with navigation services, reservation and contact forms, photo and video galleries, and review and testimonial columns from visitors. The use of responsive design is also a major focus, so that the website can be easily accessed via various devices, including smartphones and tablets. After development, usability testing was carried out to ensure that this website can provide an optimal user experience. The test results show that this website is effective in providing information needed by prospective tourists, and contributes positively to increasing visitor interest. With this website, it is expected that the number of visits to Umbul Mabar Baths will increase significantly, so that it can support the growth of the tourism sector in Marihat Bandar Village and Simalungun Regency as a whole. Keywords : Website Design, Tourist Attractions, Umbul Mabar Baths, Marihat Bandar Village, Digital Promotion, Increasing Visitors